Total leadership : be a better leader, have a richer life (with new preface) - Friedman, Stewart D. (Boston, Massachusetts : Harvard Business Review Press, 2014)
"Now in paperback, this national bestseller proves more than ever, your success as a leader isn't just about being great at business. You must be a great person, performing well in all domains of your life-including work, home, community, and your private self. The good news is that, contrary to conventional wisdom about "balance," you don't have to assume that these domains compete in a zero-sum game. Total Leadership is a game-changing blueprint for how to perform well as a leader not by trading off one domain for another, but by finding mutual value among all four. Stew Friedman shows you how to achieve these "four-way wins" as a leader who can be real, be whole, and be innovative. With engaging examples and clear instruction, Friedman provides more than thirty hands-on tools for using these proven principles to produce stronger business results, find clearer purpose in what you do, feel more connected to the people who matter most, and generate sustainable change. Total Leadership is a unique resource that shows how to win in all domains of life. "--
"Now more than ever, your success as a leader isn't just about being a great business person. You've got to be a great person, performing well in all domains of your life -- your work, your home, your community, and your private self. That's a tall order. The good news is that, contrary to conventional wisdom about "balance," you don't have to assume that these domains compete in a zero-sum game. Total Leadership is a game-changing blueprint for how to perform well as a leader not by trading off one domain for another, but by finding mutual value among all four. Stew Friedman shows you how to achieve these "four-way wins" as a leader who can: Be real: Act with authenticity by clarifying what's important Be whole: Act with integrity by respecting the whole person Be innovative: Act with creativity by experimenting to find new solutions With engaging examples and clear instruction, Friedman provides more than thirty hands-on tools for using these proven principles to produce stronger business results, find clearer purpose in what you do, feel more connected to the people who matter most, and generate sustainable change. Most leadership development books focus only on your professional skills, while books about personal growth concentrate on your needs beyond work. Total Leadership is different. It's a unique and long-awaited resource that shows how to win in all domains of life"--
Description based on print version record.
Keywords: Leadership -- Psychological aspects; Executives -- Conduct of life; Quality of work life; Work and family; Self-actualization (Psychology) -- Problems, exercises, etc; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Skills; BUSINESS & ECONOMICS / Motivational; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books